A single‐center report of COVID‐19 disease course and management in liver transplanted pediatric patients. (2nd June 2021) - Yuksel, Muhammed; Akturk, Hacer; Mizikoglu, Ozlem; Toroslu, Ertug; Arikan, Cigdem
Abstract: Background: In 2019, SARS‐CoV‐2 causing COVID‐19 emerged. Severe COVID‐19 symptoms may evolve by virtue of hyperactivation of the immune system. Equally, immunocompromised patients may be at increased risk to develop COVID‐19. However, treatment guidelines for children following liver transplantation are elusive. Methods: As a liver transplantation center, we diagnosed and followed up 10 children (male/female: 8/2) with a median age of 8.5 years (IQR: 5.2–11.0), with COVID‐19 post‐liver transplant between March 2019 and December 2020. COVID‐19 diagnosis was based on PCR test and or florid X‐ray findings compatible with COVID‐19 in the absence of other cause. We retrospectively collected clinical and laboratory data from electronic patient records following written consent from patients/parents. Results: Nine patients were diagnosed as definitive (PCR positive) with one patient being diagnosed as probable COVID‐19. Seven patients recovered without any support whereas three were admitted for non‐invasive oxygenation. Lymphopenia and/or high levels of serum IL‐6 were detected in four patients. Six patients mounted anti‐SARS‐CoV‐2 antibodies at median 30 days (IQR: 26.5–119.0) following COVID‐19 diagnosis. Antibiotic therapy, favipiravir, anakinra, and IVIG were used as treatment in 4, 1, 1 and 2 patients, respectively. Furthermore, we kept the tacrolimus with or without everolimus but stopped MMF in 2 patients. Importantly, liver allograft function was retained in all patients. Conclusions: We found that being immunocompromised did not affect disease severity nor survival. Stopping MMF yet continuing with tacrolimus was an apt treatment modality in these patients.